(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Osteoarthrosis (OA) is a chronic joint disorder marked by the primary breakdown of articular cartilage, alterations in the subchondral bone structure with the formation of new bony growths called osteophytes, inflammation of the synovial membrane (synovitis), and damage to the surrounding soft tissues.Current understanding suggests that OA develops due to multiple factors, primarily involving an imbalance between the breakdown and repair processes within the cartilage and subchondral bone. This imbalance ultimately causes cartilage deterioration and typical changes in the subchondral bone. Among all degenerative joint conditions, OA represents 12.3%, making it somewhat less prevalent than inflammatory joint diseases, which constitute about 17.7% of cases.